2010
DOI: 10.1177/0163443709350099
|View full text |Cite
|
Sign up to set email alerts
|

Speaking up or being heard? Community media interventions and the politics of listening

Abstract: Media research has generally focused more attention on analysing the 'problems' of media racism than on exploring possibilities for 'solutions' or change. In this article I introduce community media interventions as an underdeveloped and highly productive field of research into both the possibilities and the limitations of working for media change in the context of the 'war on terror' and the 'globalisation of the Muslim Other' (Hage, 2007). The opening sections discuss the concept of 'community media interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 14 publications
2
46
0
2
Order By: Relevance
“…The importance of the mass media in creating and perpetuating attitudes towards ethnic minorities has been well noted in media and cultural analysis. It has been found to be especially problematic in tabloid newspapers and on talk-back radio (Bell 1993;Dreher 2010;Goodall et al 1994;Poole 2002;Richardson 2004). These representations of diversity and of minorities have been found to have substantive impacts on the well-being and belonging of those who are portrayed adversely (Nairn et al 2006;Paradies et al 2008).…”
Section: Mass Media and Place Impactsmentioning
confidence: 99%
“…The importance of the mass media in creating and perpetuating attitudes towards ethnic minorities has been well noted in media and cultural analysis. It has been found to be especially problematic in tabloid newspapers and on talk-back radio (Bell 1993;Dreher 2010;Goodall et al 1994;Poole 2002;Richardson 2004). These representations of diversity and of minorities have been found to have substantive impacts on the well-being and belonging of those who are portrayed adversely (Nairn et al 2006;Paradies et al 2008).…”
Section: Mass Media and Place Impactsmentioning
confidence: 99%
“…Bickford's framing of the concept 'political listening' as openness, courage and continuation to value the voices of marginalised people so they have a chance to be heard, showcases the ideal environment (Bickford, 1996, p. 170). Whereas Dreher (2010) argues institutions must initiate opportunities to listen to ethnic minorities by privileging their opportunity to be heard given they are better placed to resource the communication process, Macnamara (2014, p. 9) found that while the communication field values a two-way dialogic approach to the exchange, listening is narrowly conceived as engagement and haphazardly applied by organisations as their need arises. The exchange while two-way is not equal.…”
Section: Reviewing Perspectives That Challenge a Culture Of Inclusionmentioning
confidence: 99%
“…While a keenness to engage is fundamental, it is critical to address the power disparity between organisations and their diverse publics so their voice is included. A focus on 'political listening' in order to privilege an exchange between diverse publics and managers requires facilitation by the organisation (Bickford, 1996, p. 179;Dreher, 2010). Success lies with managements' ability to establish a culture that proactively seeks multiple ways to engage.…”
Section: Building Capacity Of Organisations and Their Diverse Publicsmentioning
confidence: 99%
“…However, our own inquiry does not take for granted the idea that these myriad architectures, deployed against different challenges in different contexts, are facilitating or interacting with the idea of "voice" in the same manner. Even as ICTs enable the production and sharing of plurality of voices, they also raise questions about the "politics of listening" (Dreher, 2009(Dreher, , 2010 which cautions that an ability to speak up does not always carry with it an assurance of being heard. The challenges that participatory "voices" face in being heard and recognized are an integral obstacle in raising a participatory media's profile.…”
Section: Figurative Not Literal Voicementioning
confidence: 99%